The Effect of Recruitment and Training on Employee Performance at PT Gajah Mada Barokah Sukses Makmur Yogyakarta - Rahayu, Yunita; Manurung, John Sihar (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the influence of recruitment and training on employee performance at PT Gajah Mada Barokah Sukses Makmur (GM Production Indonesia) in Yogyakarta. The research background is based on the phenomenon of a mismatch between the number of applicants and the quality of human resources required by the company, which operates in a dynamic and competitive event organizer industry. Despite receiving thousands of applicants, only a few qualified to be hired. Therefore, the company provides internal training to enhance employee competencies and professionalism. This research employed a quantitative approach using a survey method with 70 internal employees as respondents. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that both partially and simultaneously, recruitment and training have a positive and significant effect on employee performance. The coefficient of determination (R²) value of 0.694 indicates that 69.4% of the variance in employee performance can be explained by recruitment and training, while the remaining 30.6% is influenced by other factors. These findings emphasize that selective recruitment and targeted training are crucial in building a competent workforce in the event organizer industry.